Pedicled omental split skin graft: A novel method for reconstruction of full-thickness abdominal wall defect - Chattopadhyay Anindya; Biswas Sumitra; Dutta Meghnad (Wolters Kluwer Medknow Publications, 2010)
Although rare in children, aggressive fibromatosis or desmoid tumors require wide surgical excision for durable relief. The resultant defect poses many challenges for reconstruction. The authors report reconstruction of such a wound using a pedicled omental split skin graft, which resulted from the excision of a locally recurrent desmoid tumor.